Surgical breast cancer patient pathway: Experiences of patients and relatives and their unmet needs. (12th January 2019) - Zøylner, Ingrid Annette; Lomborg, Kirsten; Christiansen, Peer Michael; Kirkegaard, Pia
Abstract: Background and aim: Breast cancer is the most common cancer disease in women worldwide. In Denmark, the law prescribes cancer patient pathways (CPPs) in general and thus also for breast cancer. Although results from patient satisfaction surveys show overall satisfaction with the pathway, a call for improvement has been voiced for some areas. The aim of this study was to explore patients' and relatives' experiences with the surgical breast CPP and to identify any unmet needs. Method: This study was based on focus groups with patients who had surgery for breast cancer, and their relatives. The settings were two Danish surgical breast cancer clinics. Findings: Overall, patients and relatives found the structure of the surgical breast CPP satisfactory. The time in the surgical department was short, and most patients found it difficult to cope with the situation. Empathy and a supportive relationship between patients, relatives and health‐care professionals were of great importance. Five key points were identified in which some of the participants had unmet needs. Suggestions for change were related to information, communication, choice of treatment, flexibility in the pathway and easy access to the clinic after surgery. Conclusion: Although patients and relatives found the CPP for breast cancer satisfactory and well planned, suggestions for change were made relating to unmet needs with respect to five key points in the pathway. Implementing findings from this study in clinical practice requires co‐operation between health‐care professionals and support from the leaders of the organization.